PERBEDAAN KOMPETENSI SOSIAL GURU MATEMATIKA SMP NEGERI DI KOTA BALIKPAPAN, KALIMANTAN TIMUR - Yuniarti, Suci (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACTThis study aims to determine differences in social competence Junior High School math teacher in Balikpapan based on class rank and gender. This research is a quantitative comparative studies. Samples were taken by using sampling techniques saturated as many as 100 teachers of mathematics Junior High School in the city of Balikpapan which follows the assessment of teacher performance in 2014. Data were analyzed using descriptive statistics and t-test. The results showed that there are differences in social competence of teachers significantly by class rank (t=-3.435, Sig.=0.001. While the social competence of teachers by gender has no significant difference (t = 1.322, Sig.=0.191). Key Words: Social competence , Junior high math teacher , The group ranks, Gender.